2011
DOI: 10.3892/etm.2011.305
|View full text |Cite
|
Sign up to set email alerts
|

Long-term protective effects of the angiotensin receptor blocker telmisartan on epirubicin-induced inflammation, oxidative stress and myocardial dysfunction

Abstract: Abstract. Chronic inflammation, oxidative stress and the renin-angiotensin system (RAS) play a significant role in chemotherapy-induced cardiotoxicity (CTX). Telmisartan (TEL), an antagonist of the angiotensin II type-1 receptor, was found to reduce anthracycline (ANT)-induced CTX. We carried out a phase II placebo (PLA)-controlled randomized trial to assess the possible role of TEL in the prevention of cardiac subclinical damage induced by epirubicin (EPI). Forty-nine patients (mean age ± SD, 53.0±8 years), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 24 publications
1
25
0
4
Order By: Relevance
“…The evidence for cardioprotection from angiotensin receptor blocker administration is scarce because their effects have been assessed in only 2 small studies in low-risk patients, one of them during just 1 week of follow-up. [69][70][71] An ongoing study is testing the cardioprotective effects of candesartan during trastuzumab therapy (http://www.clinicaltrials. gov; NCT00459771).…”
Section: Administration Of Cardioprotective Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence for cardioprotection from angiotensin receptor blocker administration is scarce because their effects have been assessed in only 2 small studies in low-risk patients, one of them during just 1 week of follow-up. [69][70][71] An ongoing study is testing the cardioprotective effects of candesartan during trastuzumab therapy (http://www.clinicaltrials. gov; NCT00459771).…”
Section: Administration Of Cardioprotective Drugsmentioning
confidence: 99%
“…76 Finally, a study has recently reported the preventive effects of spironolactone on anthracycline-induced myocardial toxicity in patients with breast cancer. 77 Important limitations of all of these studies [67][68][69][70][71][72][73][74][75][76][77][78] include the small number of patients treated, differences in study design, varying malignancies being studied and chemotherapy regimens used, and short follow-up times. In addition, in most studies, the mortality rate was lower than expected, and the reported beneficial effects on the incidence of HF and LVEF decline did not translate to lower mortality ( Table 2).…”
Section: Administration Of Cardioprotective Drugsmentioning
confidence: 99%
“…This was caused by myocardial ischemia and severe pneumonia in 2 patients each, another patient was in a generally reduced condition. Two vascular events happened within 6 months after chemotherapy, a cerebral bleeding during [35][36][37] A Grade III/IV hematotoxicity was observed in 52%. However, febrile neutropenia was observed in only 1 case.…”
Section: Discussionmentioning
confidence: 99%
“…Therapie-Responder hatten zudem weniger kardiale Ereignisse. In einer weiteren kontrollierten Studie wurde die Wirksamkeit von Telmisartan bei Epirubicin-induziertem frühem Myokardschaden untersucht [50]. Mit dem Sartan konnte im Vergleich zu Placebo die LVEF signifikant besser stabilisiert werden und erreichte nach einem Follow-up von 12 Monaten wieder den Normbereich.…”
Section: Referentin: Georgia Schilling Freiburg Ibrunclassified